Research handbook on international conflict and security law : jus ad bellum, jus in bello and jus post bellum - White, Nigel D., 1961-; Henderson, Christian (Cheltenham, UK : Edward Elgar, 2013)
Featuring some of the fields most expert thinkers, this is an adroitly constructed volume of essays in'conflict and security law'. The writing here offers a distillation of the major legal projects in the area while dissolving some of international laws most rigid demarcations (e.g. between war and peace, or the jus ad bellum and jus in bello). Gerry Simpson, University of Melbourne, Australia A most important and timely collection of essays that places the established international rules in their modern and challenging of context. Philippe Sands QC, University College London, UK Events of the past fifteen years have sharpened the focus on well-known issues in international conflict and security law. What responses to international terrorism are permissible? Can humanitarian intervention be justified under international law? The Research Handbook on International Conflict and Security Law addresses these and other debates across the areas of conflict prevention, use of force and post-conflict reconstruction, with the critical insight for which the contributors are known. James Crawford, University of Cambridge, UK This innovative Research Handbook brings together leading international law scholars from around the world to discuss and highlight the contemporary debate regarding issues of conflict prevention and the legality of resorting to the use of armed force through to those arising during an armed conflict and in the phase between conflict and peace. The Handbook covers key conceptual topics drawn from across the three areas of jus ad bellum, jus in bello and jus post bellum. The subject matter of the included chapters range from conflict prevention through to reparation and compensation, via coverage of issues such as disarmament, the role of the Security Council, self-defence, humanitarian intervention and the responsibility to protect, targets, war crimes, private military contractors, peacekeeping, and the protection of human rights. Being the first to examine topics under these areas in one volume, the book will be of interest to scholars, academics, postgraduate and research students as well as government lawyers from various disciplinary backgrounds looking for a contemporary grounding in issues under the broad theme of international conflict and security law.
Introduction: International conflict and security law / Christian Henderson and Nigel D. White -- Conflict prevention / Kenneth Manusama -- Disarmament and non-proliferation / Mirko Sossai -- The prohibition of threats of force / Mary Ellen O'Connell -- The centrality of the United Nations Security Council in the legal regime governing the use of force / Christian Henderson -- A study of the scope and operation of the rights of the individual and collective self-defence under international law / Dino Kritsiotis -- The use of force for humanitarian purposes / Christine Gray -- A taxonomy of armed conflict / Marko Mlanovic and Vidan Hadzi-Vidanovic -- Weapons / Karen Hulme -- Targets / David Turns -- Protected persons in international armed conflicts / Tom Ruys and Christian De Cock -- Private military companies / Chia Lehnardt -- International humanitarian law and human rights law / Matthew Happold -- War crimes / Robert Cryer -- Peace settlements and international law : from lex pacificatoria to jus post bellum / Christine Bell -- Foreign territorial administration and international trusteeship over people : colonialism, occupation, the mandates and trusteeship arrangements, and international territorial administration / Ralph Wilde -- Peacekeeping or war-fighting / Nigel D. White -- Human rights protection during extra-territorial military operations : perspectives at international and English law / Alexander Orakhelashvili -- Reparation and compensation / Natalino Ronzitti.
Includes bibliographical references and index.
Keywords: War (International law); Security, International; Just war doctrine; Peace-building -- Law and legislation